Signal Transducer and Activator of Transcription 3 Control of Human T and B Cell Responses - Deenick, Elissa K.; Pelham, Simon J.; Kane, Alisa; Ma, Cindy S. (Frontiers in Immunology, 2018)
Signal transducer and activator of transcription 3 (STAT3) is a transcription factor that is activated downstream of many key cytokine receptors expressed by lymphocytes. As such it plays a critical role in regulating B cells as well as CD4+ and CD8+ T cells. Patients with clinically significant immunodeficiency and immune dysregulation resulting from loss of function or gain of function mutations in STAT3 have been described. These individuals provide insight into the critical role of this transcription factor in the regulation of immune responses and the balance between effective immune protection and autoimmunity.